Evaluasi Ruang Terbuka Di Kampus Universitas Brawijaya - Laksmiwati, Triandi; Amiuza, Chairil Budiarto; Astrini, Wulan (RUAS, 2013)
The post occupancy evaluation (POE) of campus open space aimed to asses comfort space both physically and perceptionally. Open spaces choosen as case study are court and gazebo in front of rectorate building of Brawijaya University. This study combines qualitative approaches with a survey method. The research instruments are photos, questionnaires, and interviews. Respondents in this study were selected by purposive sampling. Data obtained from respondents were processed to obtain description of the behavior of open space users. Interpretation of the results was analyzed in order to obtain an overall description of the space efficiency for its users. The results obtained indicate that gazebo unable to accomodate users’ comfort of campuss open space of UB on privacy and perception aspects. Besides, interaction aspect of gazebo able to accomodate users’ comfort of campus open space of UB in good level (more than 50%), while orientation aspect able to accomodate it in medium level (50%). The court is unable to accomodate users’ comfort (less than 50%).Keywords: POE, open space, campus